Increasing the productivity of the wire-cut electrical discharge machine associated with sustainable production - Maher, I.; Sarhan, A.A.D.; Barzani, M.M.; Hamdi, M. (Elsevier, 2015)
Wire-cut electric discharge machining is a nontraditional technique by which the required profile is acquired using sparks energy. Concerning wire-cut electric discharge machining, high cutting rates and precision machining is necessary to improve productivity and achieve high quality of machined workpieces. In this research work, an experimental investigation was introduced to achieve higher productivity of the wire electrode associated with sustainable production in terms of product quality and less heat-affected zone. For this purpose, the effects of machining parameters including peak current, pulse on time and wire preloading were investigated using adaptive neuro-fuzzy inference system along with the Taguchi method. From this study, the optimal setting of machining parameters to achieve higher productivity and sustainability was identified. Moreover, Neuro-fuzzy modeling was successfully used to build an empirical model for the selection of machining parameters to achieve higher productivity at highest possible surface quality and minimum cost for sustainable production. (C) 2015 Elsevier Ltd. All rights reserved.